PENGARUH PENERAPAN METODE KONTEN E-LEARNING PADA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Nurgufriani, Anita; Adiansha, Adi Apriadi; Borolla, Vridolin Vrosansen; Uyun, Nurul (Universitas Lampung, 2023)
This research aims to determine the impact of implementing e-learning content method on learning outcomes and the effectiveness of learning in achieving student learning outcomes at SDN Inpres Pela. The research method utilizes a quasi-experimental approach with a nonequivalent control group design, involving class VA (experimental group) applying the e-learning content method and class VB (control group) using conventional teaching methods. Evaluation of learning outcomes involves pre-tests and post-tests, as well as descriptive data analysis encompassing mean, median, variance, and standard deviation. Furthermore, requirement analysis is conducted through tests of homogeneity and normality. The research results reveal a significant improvement of 53.18% in the experimental group, with a substantial increase of 71.59% in learning outcomes compared to the control group. This study strengthens the evidence that the use of e-learning content in the learning process has a significantly positive impact on student learning outcomes. It provides a deeper understanding of the benefits of the e-learning content method in enhancing student learning achievements at SDN Inpres Pela.